The TWEAK-Fn14 Ligand Receptor Axis Promotes Glioblastoma Cell Invasion and Survival Via Activation of Multiple GEF-Rho GTPase Signaling Systems - Fortin Ensign, Shannon Patricia (The University of Arizona., 2013)
Glioblastoma (GB) is the highest grade and most common form of primary adult brain tumors, characterized by a highly invasive cell population. GB tumors develop treatment resistance and ultimately recur; the median survival is nearly fifteen months and importantly, the invading cell population is attributed with having a decreased sensitivity to therapeutics. Thus, there remains a necessity to identify the genetic and signaling mechanisms that promote tumor spread and therapeutic resistance in order to develop new targeted treatment strategies to combat this rapidly progressive disease. TWEAK-Fn14 ligand-receptor signaling is one mechanism in GB that promotes cell invasiveness and survival, and is dependent upon the activity of multiple Rho GTPases including Rac1. Here, we show that Cdc42 is essential in Fn14-mediated Rac1 activation. We identified two guanine nucleotide exchange factors (GEFs), Ect2 and Trio, involved in the TWEAK-induced activation of Cdc42 and Rac1, respectively, as well as in the subsequent TWEAK-Fn14 directed glioma cell migration and invasion. In addition, we characterized the role of SGEF in promoting Fn14-induced Rac1 activation. SGEF, a RhoG-specific GEF, is overexpressed in GB tumors and promotes TWEAK-Fn14-mediated glioma invasion. Moreover, we characterized the correlation between SGEF expression and TMZ resistance, and defined a role for SGEF in promoting the survival of glioma cells. SGEF mRNA and protein expression are regulated by the TWEAK-Fn14 signaling axis in an NF-kB dependent manner and inhibition of SGEF expression sensitizes glioma cells to TMZ treatment. Lastly, gene expression analysis of SGEF depleted GB cells revealed altered expression of a network of DNA repair and survival genes. Thus TWEAK-Fn14 signaling through the GEF-Rho GTPase systems which include the Ect2, Trio, and SGEF activation of Cdc42 and/or Rac1 presents a pathway of attractive drug targets in glioma therapy, and SGEF signaling represents a novel target in the setting of TMZ refractory, invasive GB cells.